Dijkstra Algorithm Implementation to Determine the Shortest Route to Hospital: A Case Study in Magelang District Indonesia - Kurniawan, Febri; Widyanto, R. Arri; Sukmasetya, Pristi (E3S web of conferences, 2024)
Digital maps are an important tool used to find a place. The use of digital maps is very diverse, including to provide routes from one place to another. The map can also show that the route is heavy with traffic so that another route can be found. However, sometimes maps provide unclear routes so users can get lost. Users will search for the nearest hospital on the map. The map will display all hospitals, but the user must choose the hospital to go to and then follow the suggested route. This is of course very inconvenient if in an emergency you have to find the location of the nearest hospital, so you need an application that can show the exact location of the hospital. The purpose of this research is to determine the shortest route to the nearest hospital so as to save time in an emergency. The method used in this research is using Dijkstra's algorithm. Current location search and the shortest route to the nearest hospital. The calculation results obtained a value of 0.476 km which indicates the shortest route. The application of Dijkstra's algorithm can maximize the use of the map with the shortest route to the nearest hospital.